Carnival - Richardson, Betsy (Richardson, Betsy. Celebrating holidays & festivals around the world., 2019)
Examines the history of Carnival as a cultural celebration of the good and pleasurable things in life, discussing how it is celebrated across the world in Christianity, Eastern Europe, and to the Americas--with elaborate floats, street marching, colorful costumes, and lots of good food and music.